Concentration of the voting power and market capitalization: the case of PSI 15 - Quaresma, Ana (2022)
Good Corporate Governance Practices are seen as influencing the good performance of organizations. In listed companies, with the social capital open to investors, their adoption is even more relevant because the market up prices companies that comply with the recommendations in this matter and penalizes those whose corporate governance is not guided by the best corporate governance practices. The Boards of Directors, being the link between the company and its investors/shareholders, are responsible for compliance with Good Corporate Governance Practices, thus attracting investors with an positive impact on the growth and sustainability of organizations. There are several recommendations to the Boards of Directors for the good governance of companies. In this study, we took as a sample the companies that make up the PSI 15, Euronext Lisbon Stock Index, and verified whether the Corporate Governance variable: CONPOV (concentration of voting power) influenced the Market Capitalization of the organizations under study. It was found that most of the companies under study have a high CONPOV index and that they are the ones that achieve a higher market capitalization, highlighting a positive correlation between the